The Effect of Financial Literacy, Technology Financial Literacy and Financial Inclusion on MSME Performance - Pranisya, Rizal; Sari, Pristin Prima; Maulida, Alfiatul (Jurnal Ekonomi dan Bisnis, 2024)
Financial management is key in the performance of MSMEs where if business owners cannot manage their finances, it is certain that their business performance will not run well. In order for MSME businesses to run well, it is very necessary for business actors to understand financial literacy, financial technology and financial inclusion that can improve the performance of MSMEs. Finance to get welfare for MSME actors. This study aims to determine the effect of financial literacy, fintech and financial inclusion on the performance of MSMEs in Yogyakarta City. The research method uses quantitative, the population in this study were MSMEs in the City of Yogyakarta. The sample of this research is Micro MSMEs in Yogyakarta City and has a maximum of 5 employees, the sampling technique used purposive sampling with the Slovin formula with a standard error of 10% so that a sample size 63 businesses was obtained. The analysis tool used for testing is SPSS version 25. The results showed that financial literacy and financial inclusion had a positive and significant effect on the performance of micro MSMEs in Yogyakarta City while fintech had no positive and significant effect on the performance of micro MSMEs in Yogyakarta City. The three variables namely financial literacy, financial literacy technology and financial inclusion as a whole have a simultaneous influence on the performance of micro MSMEs in Yogyakarta City.